MENTAL HEALTH CORNER DALAM UPAYA DETEKSI DINI DAN PENGUATAN KESEHATAN MENTAL PADA REMAJA: MENTAL HEALTH CORNER DALAM UPAYA DETEKSI DINI DAN PENGUATAN KESEHATAN MENTAL PADA REMAJA - M.Elyas Arif Budiman; Zidni Nuris Yuhbaba; Wahyi Sholehah Erdah Suswati (LPPM Universitas dr. Soebandi, 2023)
Adolescents who live in this modern era increasingly need mental toughness to face the living conditions of the 21st century which are full of very fast changes. For this reason, schools as educational institutions need to make efforts to help improve the mental health of adolescents, so that they are able to become resilient teenagers in the midst of stressful life situations and environments. The purpose of this Community Service is to improve the mental health of adolescents. Preparation for the implementation of the activity began with an introduction related to the study of the latest phenomena that were developing and continued with coordination with the Jember Regency political and national association bodies and continued coordination with the MAN (Islamic school) of Jember Regency. Community service activities are packaged with the Mental Health Corner event which is a pattern of mental health education training methods through screening activities, health education and direct counseling. The instruments used were a knowledge instrument on mental health problems and a modified The Patient Health Questionnaire (PHQ) questionnaire. The pretest results of adolescent knowledge about mental health were in the category of 55% bad knowledge and 45% good knowledge. Posttest results from community service activities increased the level of knowledge of adolescents, namely good knowledge by 62% and bad knowledge by 38%. The mental health corner is one of the media that can be accessed by adolescents in improving mental health status. Screening and education in mental health corner activities provide facilities and opportunities for youth to become more familiar with health.